Analysis of Albumin Content, Protein Molecular Weight Profile, Heavy Metal Content, and Escherichia coli Contamination in Liquid Extract of Snakehead Fish (Channa striata) in Karawang Regency - Mukhaimin, Iman; Wulansari, Devi; Ratnaningtyas, Susi; Panjaitan, Tina Fransiskha Caroline (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
The Snakehead fish extract is one of the fish extracts that has many benefits and has been used in the health sector such as emulsifiers, skin health drugs, helping muscle formation and growth, accelerating wound healing, maintaining fluid balance in blood vessels, improving poor nutrition, and being healthy. for digestion so that the quality characteristics of the extract need to be researched and maintained to be used. This study aims to determine the quality characteristics of the liquid extract of snakehead fish (Channa striata) based on quality parameters such as protein molecular weight profile, heavy metal contamination of lead (Pb), and cadmium (Cd), and bacterial contamination of Escherichia coli. Snakehead fish extract was obtained using the steaming extraction method at a temperature of 60oC, for 6 hours to obtain albumin levels of 12.549 mg/g, protein molecular weight profile analysis detected 7 major bands and 1 minor band in the molecular weight range 19.05 kDa - 92, 72 kDa, where the molecular weight of albumin protein is suspected to be in band number 3 53.72 kDa, E.coli bacteria contamination < 3 APM/g and heavy metals lead (Pb), and cadmium (Cd) were not detected.